Growth and Development of Health Insurance in India - Rani, Poonam; Chauhan, Payal (Journal of Commerce and Trade, 2022)
A person or a group can acquire health insurance in advance after paying a charge known as a "premium." It is an additional funding source for expanding access to high-quality healthcare. Health insurance products is offered by general insurance and life insurance companies in India. A nation's health indicators are evaluated using factors such as fatality rate, pregnancy-related death. Since independence, India has made significant progress in every sector. However, according to the 11th Plan, the country's healthcare services cost was higher in private industry than in the public sector. To lighten the burden on the poor, a study group formed by the Ministry of Health recommended investigating a risk pooling scheme. This paper is based on growth and development of health insurance in India. Secondary data has been used for the study purpose and collected from various sources. This study is completely based on secondary data. The data was collected from reports published by WHO, IRDA, research articles and review articles pertaining to the health insurance industry in India. The market for health insurance in India is primarily untapped. The main target population is the medium-income group, which provides the brightest future for this industry. Classification-JEL: I12, I13